Plastics: are they part of the zero-waste agenda or the toxic-waste agenda? - Zaman, Atiq; Newman, Peter (BMC-Bio Med Centre, 2021)
Background: Plastics were considered as a magical material owing to their strong, non-degradable and versatile characteristics. After five decades of mass application, plastics’ property of non-biodegradability has become one of the key concerns for scientists, civil society and government owing to the pollution and damage that plastics cause to our environment. Globally we have generated 8.3bn tonnes of plastics since 1950s and around 9% has been recycled, 12% incinerated and the remaining 79% of the plastics has ended up in the environment. The core question is, should this waste be minimised through the zero-waste agenda or banned through the toxic-waste agenda?